Pattern of Anti-Microbial Sensitivity and Resistance against Salmonella Species in a Tertiary Hospital in Dhaka (Journal of Enam Medical College, 2015)
Background: Drug resistant Salmonella spp. continues to remain a health problem as last two decades have witnessed the emergence and spread of multidrug resistance against conventional anti-typhoid drugs. Multidrug resistant (MDR) typhoid is now a serious problem in many developing countries including Bangladesh.Objectives: To find out antimicrobial sensitivity and resistance patterns of different types of Salmonella spp. in patients with enteric fever and to find out the epidemiological strains (e.g. resistant strain, epidemic strain, MDR strain) in patients with enteric fever.Materials and Methods: This cross-sectional study was done during October 2009November 2010 and JanuaryDecember 2012 at United Hospital Limited, Dhaka. Laboratory reports of blood culture were collected from those patients who were investigated as suspected cases of enteric fever. Both the indoor and outdoor patients were enrolled in the study. Salmonella species resistant to one or more of the first line drugs were divided into resistant strain, epidemic strain and multi-drug resistant strain.Results: During the period October 2009November 2010, total 210 subjects were enrolled. Among the participants, 122 were male and 88 were female. S. typhi were found in 133 samples whereas 76 were S. paratyphi A and only 1 S. paratyphi B. Sensitivity was found 77% for ampicillin, 91.4% for cotrimoxazole, 78.6% for chloramphenicol, 87.6% for ciprofloxacin, 96.6% for cefixime, 98% for ceftriaxone and only 22.1% for azithromycin (77.9% resistant). Total 91 (43.3%) cases were found having resistant strain, 6 (2.8%) epidemic strain and 8 (3.8%) MDR strain Salmonella spp. The sensitivity of azithromycin was analyzed among different categories of strains and revealed that 52.7% showed resistance in resistant strain, 100% in epidemic strain and 87.5% in MDR strain. During the period between JanuaryDecember 2012, total 139 subjects were enrolled. Among the participants 68 were male and 71 were female with a ratio of 1:1.04. S. typhi were found in 84 cases whereas 55 were S. paratyphi A and no S. paratyphi B. Sensitivity was found 62.7% for ampicillin, 82% for cotrimoxazole, 83% for chloramphenicol, 45.2% for azithromycin, 95% for ciprofloxacin, 99.3% for cefixime and 100% for ceftriaxone. Total 55 (39.6%) cases were found having resistant strain, 3 (2.1%) epidemic strain and 17 (12.2%) MDR strain Salmonella spp. Against azithromycin 67.3% showed resistance in resistant strain, 33.3% in epidemic strain and 29.4% in MDR strain.Conclusion: The policy of empirical treatment of enteric fever needs to be rationalized and newer generation antibiotics should be restricted only for multi-resistant cases of enteric fever.J Enam Med Col 2015; 5(2): 88-92